APPLICATION OF GENERALIZED EXTREME VALUE DISTRIBUTION TO ANNUAL MAXIMUM RAINFALL - Ilesanmi, Anthony O.; Halid, Omobolaji Y.; Adejuwon, Samuel O.; Odukoya, E. Ayooluwa; Olayemi, M. Sunday (FUDMA JOURNAL OF SCIENCES, 2024)
Generalized Extreme Value Distributions was used to model annual maximum rainfall data in Akure, Ondo State, Nigeria from 1981-2019. The parameters of the distribution are estimated using the maximum likelihood estimation method. The model fit indicated that the shape parameter is negative this suggests that Fréchet distribution is the appropriate model for describing annual maximum rainfall in Ondo-state Nigeria. The estimated return levels for different return periods revealed an increase in the value over the years.